The relationship between mother's knowledge and family support with the completeness of advanced immunization for toddlers at the Tambakrejo Public Health Center, Bojonegoro - Latifatul Kandini (Gema Bidan Indonesia, 2023)
Follow-up immunization is repeated immunization to maintain the level of immunity or to maintain the period of protection. Follow-up immunizations are given to children under the age of three (toddlers), elementary school-aged children and women of childbearing age. The coverage of follow-up immunization at the Tambakrejo Health Center in 2020 has decreased compared to 2021 by 14% in the follow-up immunization of DPT-HB-Hib and by 7.3% in the follow-up immunization against measles. The purpose of this study was to analyze the relationship between maternal knowledge and family support with completeness of follow-up immunizations for children under five. The type of research used is analytical research. The population in this study were all mothers who had children aged 25-30 months in the Tambakrejo Bojonegoro Health Center area as many as 179 children in February 2022. The sampling technique in this study was a simple random sampling technique. Analysis of the data used is chi square. The results showed that the mother's knowledge of advanced immunization for toddlers was mostly good as much as 62.6%. Family support regarding follow-up immunizations for toddlers is mostly good, as much as 53.7%. Almost all toddlers aged 20-3-months had complete follow-up immunization status as much as 91.9%. Most of the mothers with good knowledge and complete follow-up immunization were 57.7%, and the majority of mothers who had good family support and had complete follow-up immunizations were 52%. There is a relationship between family support and completeness of follow-up immunizations for children under five.